MODELING SUBSIDENCE ON GEOTHERMAL RESERVOIR USING STARS SIMULATOR - HARYANTO LUKMANA, ALLEN
The decrease of ground level associated with geothermal field development has been observed and studied in geothermal fields, for example in New Zealand. Deformable reservoir modeling is needed to include geomechanical influence on the geothermal reservoir model, so the model can simulate deformation and subsidence processes. The reservoir simulation in this study uses CMG-STARS® Advanced Process and Thermal Reservoir Simulator, which can model fluid flow with geomechanical influence. The purpose of this study was to investigate important parameters related to geomechanics and fluid flow. CMG-STARS® uses an iterative coupling scheme, by completing a fluid flow module and the results are used in the calculation of geomechanical modules. The synthetic model used in this study represents the geothermal reservoir model of water dominance with a total fluid production rate of 600 kg/s. After simulation done for thirty years there was a decrease of porosity, permeability and subsidence +2.4 meters in production well area. The sensitivity test was performed with geomechanical parameters and total flow rate of fluid production / injection, to see the effect on subsidence. The result of the sensitivity is known some parameters that influence the value of subsidence generated, such as the number of production flow rates, the number of flow rates of injection wells, young modulus, poisson ratio, porosity, and biot coefficient. Based on the result of research, simulator able to do geomechanical simulation and fluid flow simulation.